Vertical motion control of a one legged hopping robot by using central pattern generator (CPG) - Azahar, Arman Hadi; Chong, Shin Horng; Mohammed Kassim, Anuar (2013)
This paper presents vertical motion control of a one-legged hopping robot using Central Pattern Generator (CPG). The hopping dynamic of the hopping robot is produced by controlling the motor speed to produce force through the crank to the mass, spring, and damper. The classical controllers; PI and PID controller are designed to control the vertical motion of a one legged hopping robot. The parameters for each PI and PID controller are determined by using Ziegler-Nichols method. However, the outputs produced by the controllers do not reach the desired input. Therefore, a CPG model is designed to integrate with these controllers in order to control the hopping robot. The CPG implementation in a mass-spring-damper model is extended to investigate on its dynamic mechanism and vertical motion during hopping. All of integration controller performances are analyzed based on the dynamic response of the hopping robot to reach the desired height. Statistical method is used to analyze the dynamic response. The statistical features that analyzed are mean, mod, error, minimum and maximum boundary of the hopping height produced. As a result, the integration CPG with PI controller is the best controller for the designed one legged hopping robot in term of the mean of the hopping height and error in achieving the desired height.